2007
DOI: 10.1007/bf02898027
|View full text |Cite
|
Sign up to set email alerts
|

Geonotoxicity study of illegal drug MDMA and its nitroso derivative N-MDMA by micronucleus and chromosomal aberration tests using Chinese hamsger lung fibroblast cell line

Abstract: Objectives: An increase in incidence of the illegal use of tablets containing 3,4-methylenedioxymethamphetamine hydrochloride (MDMA) has recently become a widespread social problem. MDMA ingested orally reacts with nitrite in the stomach and is synthesized into N-nitroso-3,4-methylenedioxymethamphetamine (N-MDMA). The aim of this study is to investigate the genotoxic effects of MDMA and N-MDMA on the basis of the results of an in vitro micronucleus (MN) test and an in vitro chromosomal aberration (CA) test usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…MDMA did not show any signs of genotoxicity across the three robust test systems analyzed. These results are consistent with past articles from Hariri ( Hariri et al, 2010 ) and Yoshioka ( Yoshioka et al, 2007 ). We highlight that these studies are the recommended studies to rule out genotoxicity potential by regulators internationally ( ICH Expert Working Group, 2011 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…MDMA did not show any signs of genotoxicity across the three robust test systems analyzed. These results are consistent with past articles from Hariri ( Hariri et al, 2010 ) and Yoshioka ( Yoshioka et al, 2007 ). We highlight that these studies are the recommended studies to rule out genotoxicity potential by regulators internationally ( ICH Expert Working Group, 2011 ).…”
Section: Discussionsupporting
confidence: 94%
“…Contrary to currently used psychiatric medications, MDMA is not administered daily for months or years on end, but in three divided dose exposures over the course of a few months ( Kalant, 2001 ). Currently there is mixed reporting on the absence or presence of MDMA genotoxicity in various preclinical test systems ( Barenys et al, 2009 ; Frenzilli et al, 2007 ; Hariri et al, 2010 ; Parolini et al, 2014 ; Yoshioka et al., 2007 ). In order to settle the lack of consensus in previous literature, we conducted three regulatory compliant studies investigating the genotoxic potential of MDMA in humans: (1) an in vitro bacterial reverse mutation (Ames) assay, (2) an in vitro chromosome aberration test in Chinese hamster ovary (CHO) cells, and (3) an in vivo micronucleus study in male Sprague Dawley rats.…”
Section: Introductionmentioning
confidence: 99%
“…These results agree with those obtained by Yoshioka et al on a hamster pulmonary fibroblasts cell line (CHL/IU), where the authors demonstrated, by the MN test and by the chromosomal aberration test, the genotoxicity of N-nitroso-3,4-methylenedioxymethamphetamine (N-MDMA), but not of the MDMA as such. In fact, MDMA is a secondary amine able to react in acidic environments, such as the stomach, with N-nitroso compounds, often present in many foods and other sources, to form N-nitrosamines, which are known carcinogen compounds [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the specific case of psychoactive phenethylamines, bibliographic research conducted on the main databases (i.e., Scopus from Elsevier and PubMed from MEDLINE), allowed us to identify only one publication on the in vivo genotoxicity of methamphetamine [ 38 ] and one of the cathinone mephedrone [ 39 ]. Moreover, currently, one study in vitro [ 40 ] and four studies in vivo [ 41 , 42 , 43 , 44 ] on DNA impact following the MDMA intake are reported, while, to our knowledge, there is no specific research regarding 2C-H, 2C-I, 2C-B and 25B-NBOMe.…”
Section: Introductionmentioning
confidence: 99%